(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
This study describes the chiton fauna (Mollusca, Polyplacophora) from deposits of the Miocene marine sequence of North Italy, located in Piedmont and Emilia Romagna regions. This first part of the work describes the chitons pertaining to four families: Leptochitonidae, Hanleyidae, Ischnochitonidae and Callistoplacidae. The studied fossils consist of 377 valves from 13 sites (Sciolze, Valle Ceppi, Rocco di Passerano, Albugnano, Monchio di Sarzano Casina, Villa Monti, Rio di Bocca d’Asino, Sant’Agata Fossili, Vargo, Vigoleno, Montegibbio, Borelli, and Moncucco Torinese) ranging from the Early Miocene (Burdigalian) to the Late Miocene (Messinian). We identified 16 species, 12 of which were already known, two are identified only at generic level (Stenosemus sp. A & sp. B), and two are described as new: Parachiton statianus sp. n., and Callistochiton borellianus sp. n. Some species found are particularly noteworthy; Lepidopleurus benoisti is the new name attributed to the species previously known as Middendorffia subcajetana or Gymnoplax orbignyi, based on the study of the type material; Leptochiton salicensis, previously known only from the Early Pleistocene of Salice (Messina, Sicily); Hanleya mediterranea is reported for the first time from the Miocene of Italy; Ischnochiton ligusticus, previously known only from the Early Pliocene of Western Liguria; the distribution of Stenoplax paviai, recently described from the Late Miocene (Rio di Bocca d’Asino), is extended to the Early Miocene (Langhian). A complete discussion on the chiton fauna from the North Italian Miocene, consisting of all the species treated in both parts, will be given in the second part of this work.